Dampak trauma masa kecil terhadap risiko bunuh diri pada dewasa muda - Cahyanti, Elisa Tika (Maliki Interdisciplinary Journal, 2025)
Childhood trauma is a phenomenon that is often overlooked but has a significant long-term impact on an individual’s mental health in adulthood. This issue is critical considering the increasing incidence of suicide among young adults who have a history of childhood trauma. This study aims to explore the relationship between childhood trauma and suicide risk in young adults by reviewing the available literature. This study uses a literature study method by collecting and analyzing data from various scientific journals that comprehensively discuss childhood trauma, its psychological impacts, and its relationship to suicidal behavior in young adulthood. The results of the study revealed that individuals who experienced childhood trauma, such as physical, emotional, or sexual abuse, as well as neglect experiences, have a higher risk of experiencing mental disorders that lead to suicidal behavior. These findings emphasize the importance of early intervention and appropriate treatment of childhood trauma to prevent the risk of suicide later in life.